Multiple factors dominate the distribution of methane and its sea-to-air flux in the Bohai Sea in summer and autumn of 2014. (May 2020) - Zang, Kunpeng; Zhang, Guiling; Zhao, Huade; Xu, Xuemei; Zheng, Nan; Wang, Juying; Zhang, Gen
Abstract: The Bohai Sea is well-known as a source of atmospheric methane (CH4 ). However, the main regulate factors of the spatiotemporal distribution of CH4 and its sea-to-air flux remain largely unknown. In this study, the observed CH4 concentration ranged from 4.8 to 32.7 nmol/L and 3.1 to 15.2 nmol/L in August and November of 2014, respectively. The main factors that influence the distribution of CH4 and its sea-to-air flux were stratification, solubility, and current structure for the mid-west depression basins, the permanent well-mixed seawater column and CH4 source strength for the centre shallow ridge zone, and the upwelling for the east depression basin, respectively. Meanwhile, wind also plays an important role in sea-to-air CH4 flux in the study area except the centre shallow ridge zone. Upwelling made the east depression basin the most intensive source of CH4, with a flux of 2 to 4 times higher than the other sub-regions. Graphical abstract: Unlabelled Image Highlights: CH4 concentration distribution and its flux were impacted by multiple factors. Stratification dominated the accumulation of CH4 in bottom layer in summer. Permanent well-mixed water column caused a homogenous vertical distribution of CH4 . Upwelling enhanced sea-to-air CH4 flux significantly.